Evaluasi Kepuasan Pasien terhadap Pelayanan Instalasi Gizi di RS PKU Muhammadiyah Gamping Yogyakarta, Indonesia: Evaluation of Patient Satisfaction with Nutrition Installation Services at PKU Muhammadiyah Gamping Hospital Yogyakarta, Indonesia - Azwarjaya, Faturahman Fauzi; Ulfa, Maria; Razalli, Nurul Huda; Rajikan, Roslee; Akca, Nesrin; Saygili, Meltem (Amerta Nutrition, 2025)
Background: PKU Muhammadiyah Gamping Hospital, Yogyakarta, recorded an estimated food waste production of around 900 kg from January to June 2024. This data highlights the significant food-related problems in healthcare facilities and underscores the need for strategies to improve patient satisfaction. Objectives: This study aims to evaluate patient satisfaction with nutritional services at PKU Muhammadiyah Gamping Hospital, Yogyakarta. Methods: This study employed a quantitative approach, utilizing a questionnaire comprising 44 questions adapted from the Schiavone and Acute Hospital Foodservice Patient Satisfaction Questionnaire (ACHFPSQ), which was analyzed using SPSS. Respondents were patients treated at PKU Muhamadiyah Gamping Hospital, Yogyakarta. Results: The average patient satisfaction with food quality based on Schiavone was 3.64±0.83, and the average patient satisfaction with food quality based on the ACHFPSQ was 3.64±0.873. The satisfaction ratings ranged from 2.38±0.862 to 4.64±0.5. The highest rating for food prepared and distributed safely and under control was 4.28±0.573, while the lowest rating for hospital food quality expectations was 2.38±0.862. According to Schiavone, the average patient satisfaction with food service was 4.12±0.596; according to the ACHFPSQ, it was 4.45±0.486. The highest score for staff who delivered food neatly and cleanly was 4.64±0.5. The lowest score for comparing current food service quality with previous care experience was 3.50±0.723. Conclusions: The research findings indicated that patients were generally satisfied with the comprehensive nutrition services. Nevertheless, some areas require enhancement, particularly in healthy menu options and food taste quality.